Marine transgression in the Permian Pusige Formation, the southwestern Tarim Basin, China: Identification of the event and its control on lacustrine source rock development - Lin Deng; Haizu Zhang; Wen Liu; Cai Chen; Bin Cheng; Yunpeng Wang; Zewen Liao (Journal of Asian Earth Sciences, 2026)

Intelligent monitoring and management of urban drainage systems through machine-learning-driven fusion of EEM and UV-Vis - Hao-Lin Yang; Xin Zhang; Shang-Wen Deng; Jia-Min Xu; Ruo-Zhou Lin; Zhi-Yu Zhang; Yu-Qi Wang; Ding-Ding Tang; Hong-Cheng Wang (Journal of Environmental Management, 2026)

Seismic reflection profiles reveal the Changjiangbu Fault and shallow structural features in the Ying-Yun Sag, northeastern Jianghan Basin - Cong Jin; Song Lin; Xiaohu Deng; Daicheng Peng; Fei Cheng (Journal of Applied Geophysics, 2026)

Field Study of Immobilization Materials and Foliar Inhibitors: Balancing Rice Yield, Safety, and Economy in Cd-As Contaminated Soils - Junchun Li; Longyong Lin; Yirong Deng; Sheng Cheng; Xiao Yang; Xiulan Yan; Qian Yao; Cunliang Han (Water, Air, & Soil Pollution, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

KAR1 Priming Breaks Seed Dormancy by Regulating Antioxidant System and Plant Hormones Under High Temperature in Lettuce Seeds - Hongyang Wang; Fuyuan Chen; Dexin Wang; Jing Leng; Qilin Deng; Xiulan Xu; Yang Xia; Jian Ma; Shuchun Meng; Lin Cheng; Yanhong Qiu; Haijun Zhang (Journal of Plant Growth Regulation, 2026)

Migration and enrichment of rare earth elements in a mining ion-adsorption type deposit tailings under ecological restoration - Zhuoling Lin; Longyong Lin; Sheng Cheng; Gaoling Wei; Yirong Deng; Junchun Li; Guangqing Huang (Applied Geochemistry, 2026)

Deciphering the flavor chemistry of traditional and novel nattos: A multidisciplinary approach integrating amino acid profiling, volatile compound analysis, and molecular docking - Qile Zhang; Jiawei Wu; Yiu Ming Cheung; Yuhong Lin; Xinyi Deng; Minghui Li; Chufeng He; Dianjing Guo; Cheng Li; Hon Ming Lam; Wing Tak Wong (Food and Humanity, 2026)

Removal of lead and ammonia via microcapsules-based microbial induced carbonate precipitation (MC-MICP): Performance and mechanism - Zhong-Fei Xue; Chao Xu; Wen-Chieh Cheng; Lin Wang; Liang Xu; Tingting Deng; Xinyu Xu (Chemical Engineering Journal, 2026)

The emerging role of high-throughput proteomics in advancing precision medicine - Jia You; Yue-Ting Deng; Luo Chen; Lin-Bo Wang; Yu Guo; Ze-Yu Li; Jian-Feng Feng; Jin-Tai Yu; Wei Cheng (Science Bulletin, 2026)

Stable yet hydrophilic graphene oxide nanomembranes by zwitterionic reduction for dye desalination - Sagnik Das; Ziwen Zhang; Erda Deng; Emmanuel M. Nsengiyumva; Ruveen Dias; Shixian Ha; Xiao Tong; Gbassey S.A. Oteme; Shweta Singh; Kai Chen; Prathima C. Nalam; Chang-Yong Nam; et al. (Chemical Engineering Journal, 2026)

Infra-slow body-surface potentials show a group-level association with thyroid cancer - Bohan Deng; Ruili Zhang; Yuxuan Liu; Jinglao Lin; Shicong Gui; Xihao Wei; Yin Cheng; Li Zheng; Shaohua Hu; Pingping Lyu; Yubo Li; Huafen Wang (Journal of Zhejiang University-SCIENCE B, 2026)

The Time Reliable Effect of Probiotic Clostridium butyricum on the Growth of Spotted Sea Bass (Lateolabrax maculatus) - Yiqin Deng; Liwen Xu; Keng Yang; Ziyang Lin; Shujun Zang; Kui Jiang; Wangdong Li; Nabil A. Ibrahim; Hongling Ma; Changhong Cheng; Juan Feng (Probiotics and Antimicrobial Proteins, 2026)

Deciphering the shift in extreme precipitation over the lower reaches of the Yangtze River Basin: a synoptic-scale analysis - Jiao Li; Yang Zhao; Jianping Li; Lianyi Guo; Cheng Shen; Lujia Zhang; Lin Deng; Dandan Chen (Climate Dynamics, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Microbial drivers of N₂O mitigation in soils: Role of nosZ II subclades under conservation tillage and stover mulching - Da-Cheng Hao; Yaoxuan Wang; Yuanyuan Luan; Fangbo Deng; Hongtu Xie; Yongxin Lin; Xuanqi Li; Zhongjun Jia; Lianfeng Wang (Applied Soil Ecology, 2026)

Platinum-copper nanocubezyme facilitate spinal cord recovery via synchronously alleviating oxidative stress and mitigating BNIP3-mediated mitochondrial dysfunction - Xiangge Liu; Cheng Peng; Huiyi Yang; Jiajun Deng; Ping Wu; Yongchun Xiao; Li Wan; Ke Wang; Guowei Zhang; Hua Yang; Jianyu Zou; Judun Zheng; et al. (Chemical Engineering Journal, 2025)

COMPERA 2.0 risk stratification in patients with severe aortic stenosis: implication for group 2 pulmonary hypertension - Zongye Cai; Xinrui Qi; Dao Zhou; Hanyi Dai; Abuduwufuer Yidilisi; Ming Zhong; Lin Deng; Yuchao Guo; Jiaqi Fan; Qifeng Zhu; Yuxin He; Cheng Li; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Isolation and Genomic Characterisation of Lymphocystivirus platichthys1 in Brackish‐Water Cultured Spotted Seabass Lateolabrax maculatus in Zhuhai, South China - Hongling Ma; Changhong Cheng; Yiqin Deng; Zhixun Guo; Yong Li; Guangxin Liu; Huajian Lin; Liwen Xu; Juan Feng (Journal of Fish Diseases, 2025)
Lymphocystis disease virus (LCDV) stands as one of the most widespread causative agents affecting a diverse array of teleost globally. According to the literature, LCDV encompasses four species, and Lymphocystivirus paralichthys1 (known as LCDV‐C) has long been regarded as the predominant national epidemic isolate in mainland China. In this study, two instances of severe mass mortalities associated with LCDV in brackish‐water cultured juvenile spotted seabass in Zhuhai, South China, were monitored starting from early April 2023. The death toll in these two cases peaked at approximately 4000 and 10,000 fish per day, respectively, with cumulative mortalities reaching around 70% within 19 days of the disease outbreak. Based on clinical symptoms, histopathological analyses and transmission electron microscopy observations, the diseases were diagnosed as LCDV infections. The virus was isolated using the Mandarin fish fry (MFF‐1) cell line and named LCDV‐ZH04/23. Subsequently, LCDV‐ZH04/23 was roughly purified, and its entire genome was sequenced and annotated. The results indicated that ZH04/23 consists of 102,661 base pairs, encodes 108 putative viral genes and has a G/C content of 29.3%. Genomic collinearity analysis revealed that the whole genome of ZH04/23 exhibits the highest similarity (99.9%) to the well‐known Lymphocystivirus platichthys1 (LCDV‐1) from Europe, but shows significant divergence from the other three LCDV species. Collectively, this study marks the first isolation and characterisation of L. platichthys1 at the whole genome level from cases of severe mass mortalities in pond‐cultured spotted seabass in China. Moreover, it is the first to identify L. platichthys1 as an emerging pathogen in cultured spotted seabass.

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Organic nitrates in coastal aerosols: Seasonal dynamics, influencing factors, and formation pathways - Mengke Tian; Zhijian Ding; Jia Chen; Juntao Huo; Guochen Wang; Jian Xu; Hao Li; Ziwei Liu; Yunkai Wang; Nan Ye; Xiaofei Qin; Yanfen Lin; et al. (Atmospheric Environment, 2025)

Distinct responses of fungal and bacterial denitrification genes to seasonal changes, nitrogen deposition and precipitation reduction in subtropical forest soils - Qirun Chen; Fengyi Han; Maokui Lyu; Zhiwei Zeng; Yanjiang Cai; Yuheng Cheng; Zi-Yang He; Milin Deng; Jinsheng Xie; Yongxin Lin (Applied Soil Ecology, 2025)

Multi-omics analysis reveals BPF exposure causes hepatic glucose and lipid metabolism disorder in rats by disrupting energy homeostasis - Zhi Li; Yuanyuan Wu; Mingqing Qian; Bingya Zhang; Xinxin Deng; Penghui Mao; Zhonghua Fan; Xu Fang; Lin Cheng; Xuan Liu; Li Wang; Hui Liu (Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Dynamic effects of monopiles and sacrificial piles on Lagrangian residual velocity in an idealized rectangular bay - Xudong Liu; Cheng Fan; Lin Chen; Jinzhen Yu; Shuwen Zhang; Zhangliang Wei; Fangjing Deng (Ocean Engineering, 2025)

Effortless rule: Effects of oversized microplastic management on lettuce growth and the dynamics of antibiotic resistance genes from fertilization to harvest - Jing-Yuan Chen; Lin-Jie Qin; Tiao Long; Rui-Ting Wu; Shi-Hua Niu; Shuo Liu; Wei-Kang Deng; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

Unravelling the pathogenesis of Vibrio parahaemolyticus infection: impacts on antioxidant and innate immunity gene responses in Scylla paramamosain - Guangxin Liu; Ce Li; Sigang Fan; Hongling Ma; Yiqin Deng; Jianjun Jiang; Changhong Cheng; Juan Feng; Li Lin; Zhendong Qin; Zhixun Guo (Fish & Shellfish Immunology, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Nitrogen-Doped tannin carbon dots anchored NiCo-LDH composites for high-performance asymmetric supercapacitors - Shirui Wang; Jianping Deng; Menghan Li; Jiande Lin; Lu Luo; Zhanhui Yuan; Wenxue Zhang; Cheng He; Guanben Du; Weigang Zhao (Chemical Engineering Journal, 2025)

Genotyping and antimicrobial susceptibility of Aeromonas veronii isolated from aquatic animals in Sichuan, China - Kun Peng; Silu Tian; Longjun Deng; Yu Yuan; Zixuan Cheng; Tiancai Li; Keyu Zhou; Jingyi Lin; Yi Geng (Antonie van Leeuwenhoek, 2025)

2-Mercapto-1,3,4-thiadiazole-functionalized gold nanoclusters as a comparable bactericidal nanoantibiotic to vancomycin in treating methicillin-resistant Staphylococcus aureus infections - Quan-Quan Zhuang; Jia-Xin Ma; Yi-Ming Zheng; Lin-Yan Lu; Jia-Lin Yang; Qing-Qing Chen; Xiao-Li Yan; Yan-Cheng Jiang; Hao-Hua Deng; Wei Chen; Gang Liu (Chemical Engineering Journal, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Biocompatible and stretchable chitosan piezoelectric gel with antibacterial capability and motion monitoring function for Achilles tendon rupture treatment - Zhencheng Xiong; Bingqing Lin; Cheng Huang; Ao Duan; Chaoyi Zhang; Guangliang Qiang; Wenzheng Liu; Renliang Zhao; Xiangtian Deng; Dong Wang; Zilu Ge; Guanglin Wang; et al. (Carbohydrate Polymers, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

Morphology effect on the photocatalytic performance of CeO2 and insights into the degradation mechanism of tetracycline - Saisai Deng; Hui Wang; Yanmei Dong; Wenjing Cheng; Xiangang Lin; Longxia Wu; Jun Hu; Yuanxu Liu; Yangyang Li (Journal of Environmental Chemical Engineering, 2025)

High-risk nuclide screening and parameter sensitivity analysis based on numerical simulation and machine learning - Xin Zhang; Yanjun Zhang; Yu Zhang; Yuxiang Cheng; Qiangbin Liu; Hao Deng; Yongjie Ma; Lin Bai; Lei Liu (Journal of Hazardous Materials, 2024)

Deep insights into the assembly mechanisms, co-occurrence patterns, and functional roles of microbial community in wastewater treatment plants - Zi-Yan Wei; Min Feng; Ding-Xi Zhang; Cheng-Ying Jiang; Ye Deng; Zhu-Jun Wang; Kai Feng; Yang Song; Nan Zhou; Yu-Lin Wang; Shuang-Jiang Liu (Environmental Research, 2024)

Engineering microalgae for robust glycolate biosynthesis: Targeted knockout of hydroxypyruvate reductase 1 combined with optimized culture conditions enhance glycolate production in Chlamydomonas reinhardtii - Suihao Yan; Yuyong Hou; Meijie Cui; Tingfeng Cheng; Sihan Lu; Zhiyong Liu; Bicheng Deng; Weijia Liu; Menglin Shi; Liangcai Lin; Longjiang Yu; Lei Zhao (Bioresource Technology, 2024)

Genome sequencing analysis and validation of infestation-related functional genes of Vibrio parahaemolyticus LG2206 isolated from the hepatopancreas of diseased mud crab (Scylla paramamosain) in South China - Liu Guangxin; Liu Guangfeng; Li Ce; Ma Hongling; Deng Yiqin; Cheng Changhong; Jiang Jianjun; Fan Sigang; Feng Juan; Lin Li; Qin Zhendong; Guo Zhixun (Fish & Shellfish Immunology, 2024)

A systematic review and meta-analysis on the root effects and toxic mechanisms of rare earth elements - Chenyi He; Yiping Feng; Yirong Deng; Longyong Lin; Sheng Cheng (Chemosphere, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Organic light-emitting diode therapy promotes longevity through the upregulation of SIRT1 in senescence-accelerated mouse prone 8 mice - Yue-Hua Deng; Chi-Sheng Chiou; Ching-Yu Tsai; Abhinay Kumar Singh; Edlin Anahi Pelaze Achtmann; Bou-Yue Peng; Tommy Yet-Min Lin; Hsin-Chung Cheng; Pao-Chang Chiang; Win-Ping Deng (Journal of Photochemistry and Photobiology B: Biology, 2024)

The origins of odor (β-cyclocitral) under different water nutrient conditions: Algae or submerged plants? - Yu Lin; Chaoyue Cheng; Yutai Dai; Weijie Li; Jiping Chen; Mo Chen; Ping Xie; Qiang Gao; Xiaoyue Fan; Xuwei Deng (Science of The Total Environment, 2024)

Microbial strategies for effective hexavalent chromium removal: A comprehensive review - Shilin Zha; Ao Yu; Zhongbing Wang; Qi Shi; Xunniu Cheng; Chunli Liu; Chunjian Deng; Guisheng Zeng; Shenglian Luo; Zongwen Zhao; Lin Zhou (Chemical Engineering Journal, 2024)

Tumor necrosis factor receptor-associated factor 5 protects against intimal hyperplasia by regulation of macrophage polarization via directly targeting PPARγ - Wen-Lin Cheng; Sheng-ping Chao; Fang Zhao; Huan-Huan Cai; Ziyue Zeng; Jian-Lei Cao; Zhili Jin; Ke-Qiong Deng; Xiaorong Hu; Hairong Wang; Zhibing Lu (Inflammation Research, 2024)

Repair of tendons treated with peracetic acid–ethanol and gamma irradiation by EDC combined with NHS: a morphological, biochemical and biomechanical study in vitro - Rong-xing Ma; Rui-feng Li; Xiao-qiang Deng; Rui-qi Qiao; Ji-kai Li; Kun-xiu Song; Shao-lin Ji; Yong-cheng Hu (Cell and Tissue Banking, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Multifunctional self-assembled adsorption microspheres based on waste bamboo shoot shells for multi-pollutant water purification - Jie Yang; Qianxin Long; Yan Zhu; Cheng Lin; Xiaoxi Xu; Baiyang Pan; Wenya Shi; Yuyang Guo; Jianqiu Deng; Qingrong Yao; Zhongmin Wang (Environmental Research, 2024)

Pollution levels and ecological risks of PPCPs in water and sediment samples of Danjiangkou Reservoir - Haiyang Jin; Chan Yu; Li Lin; Jinghua Cheng; He Qin; Jingxiang Tao; Shengfei Deng (Environmental Science and Pollution Research, 2024)

Black phosphorus nanosheets inhibit glioblastoma cell migration and invasion through modulation of WNT/β-catenin and NOTCH signaling pathways - Yue Xiong; Chao He; Xun Lin; Ke Cheng; Fumei He; Jingxin Zhao; Mengjie Yang; Hong Gao; Fangjie He; Xiaopei Zhang; Zeqi Liu; Gan Liu; et al. (Chemical Engineering Journal, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Chronic cadmium exposure induces Parkinson-like syndrome by eliciting sphingolipid disturbance and neuroinflammation in the midbrain of C57BL/6J mice - Yudong Xu; Huihui Hong; Xiqin Lin; Tong Tong; Jingjing Zhang; Haotian He; Lingling Yang; Gaofeng Mao; Rongrong Hao; Ping Deng; Zhengping Yu; Huifeng Pi; et al. (Environmental Pollution, 2023)

Basin filling and magmatic response to the migration of two-stage rifts: New insights into the late Neoproterozoic tectonics of the northern Tarim Craton - Caiyun Wang; Hongxiang Wu; Yildirim Dilek; Yinqi Li; Fengqi Zhang; Weikang Huang; Hongdan Deng; Hanlin Chen; Xiubin Lin; Xiaogan Cheng (Precambrian Research, 2023)

Targeting mitochondrial dynamics by AZD5363 in triple-negative breast cancer MDA-MB-231 cell–derived spheres - Yingqiang Fu; Wei Dong; Yuting Xu; Lin Li; Xin Yu; Yuheng Pang; Liujia Chan; Yuhan Deng; Cheng Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Breast cancer stem cells (BCSCs) have been suggested to contribute to chemotherapeutic resistance and disease relapse in breast cancer. Thus, BCSCs represent a promising target in developing novel breast cancer treatment strategies. Mitochondrial dynamics in BCSCs were recently highlighted as an available approach for targeting BCSCs. In this study, a three-dimensional (3D) cultured breast cancer stem cell spheres model was constructed. Mitochondrial dynamics and functions were analyzed by flow cytometry and confocal microscopy. We have demonstrated that the protein levels of FIS 1 and Mitofusin 1 were significantly increased in BCSCs. Moreover, Capivasertib (AZD5363) administration could suppress Mitofusin1 expression in BCSCs. Our use of MitoTracker Orange and annexin V double-staining assay suggested that AZD5363 could induce apoptosis in BCSCs. The sensitivity of stem cell spheres to doxorubicin was investigated by CCK8 assay, and our results indicated that AZD5363 could re-sensitize BCSCs to Doxo. Flow cytometry analysis identified doxo-induced CD44 and CD133 expression in BCSCs could be suppressed by AZD5363. In combination with AZD536, doxo-induced apoptosis in the BCSCs was significantly increased. In conclusion, our study explored, for the first time, that AZD5363 could target mitochondrial dynamics in 3D cultured stem cell spheres (BCSCs) by regulating Mitofusin.

Prediction of single pile response to lateral soil movement in model test - Congyu Lin; Qijian Liu; Tao Deng; Cheng Yue; Penglu Cui (Computers and Geotechnics, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Mid-Neoproterozoic tectonic switch from orogeny to intraplate extension in NW Tarim Craton: New evidence from a composite dike of the Aksu Group - Hong-Xiang Wu; Feng-Qi Zhang; Yildirim Dilek; Han-Lin Chen; Kong-Yang Zhu; Xiu-Bin Lin; Qin-Yan Wang; Hong-Dan Deng; Xiao-Gan Cheng (Precambrian Research, 2023)

Distribution of hydrogen isotope in the soil around the Qinshan Nuclear Power Plant - Jie Liang; Wen-yu Cheng; Jing-lin Li; Xiao-chong Xue; Ke Deng; Chao-fei Liang; Lin Du; Qin Zhang; Wei Liu (Journal of Environmental Radioactivity, 2023)

Dimeric oxyberberine CT4-1 targets LINC02331 to induce cytotoxicity and inhibit chemoresistance via suppressing Wnt/β-catenin signaling in hepatocellular carcinoma - Xian Lin; Jian Chen; Xin Li; Dong Chen; Kaixuan Luo; Yongxing Deng; Dinghua Yang; Zunnan Huang; Cheng Tao (Archives of Toxicology, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Responses of microbial community to geochemical parameters on vertical depth in bioheap system of low-grade copper sulfide - Xiu-Tong Li; Zhong-Sheng Huang; Ye Huang; Zhen Jiang; Zong-Lin Liang; Hua-Qun Yin; Guang-Ji Zhang; Yan Jia; Ye Deng; Shuang-Jiang Liu; Cheng-Ying Jiang (Science of The Total Environment, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

A tris(hydroxymethyl)aminomethane-modified polyimide membrane with efficient organic solvent resistant performance and high separation selectivity for dye/salt separation - Zitian Liu; Xuesong Deng; Ligang Lin; Rongrong Qiang; Qiying Wang; Qi Cheng; Jing Yang; Xu Yang; Wensong Ma; Xinyang Li; Meina Xu; Chunhong Wang; et al. (Desalination, 2023)

Hypoxia triggers the proliferation of antibiotic resistance genes in a marine aquaculture system - Yiqin Deng; Jianjun Jiang; Yinbang Huang; Changhong Cheng; Ziyang Lin; Guangxin Liu; Zhixun Guo; Juan Feng (Science of The Total Environment, 2023)

A new catalyst CHCP-Fe2O3 for enhanced removal of tetracycline through the Fenton-like process: Economical synthesis, catalytic performance, and practicability - Jiao He; Baoyou Pei; Chenglong Deng; Dongha Huang; Bihong Lv; Cheng Peng; Genggeng Luo; JinQing Lin (Journal of Water Process Engineering, 2023)

Criticality of solid electrolyte interphase in achieving high performance of sodium-ion batteries - Qian Cheng; Qiang Deng; Wentao Zhong; Ting Tan; Xiaozhao Liu; Changdong Chen; Junhua Hu; Zhang Lin; Kevin Huang; Chenghao Yang (Chemical Engineering Journal, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Combination of highly photovoltaic and highly transparent materials enables record performance semitransparent organic solar cells - Lin Zhao; Xuexiang Huang; Yukai Wang; Sang Young Jeong; Bin Huang; Jiawei Deng; Jiabin Liu; Yujun Cheng; Han Young Woo; Feiyan Wu; Limin Chen; Lie Chen (Chemical Engineering Journal, 2023)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Isolation and identification of new source of bacteriocin-producing Lactobacillus plantarum C010 and growth kinetics of its batch fermentation - Jinyue Dai; Limin Fang; Manmin Zhang; Huaili Deng; Xin Cheng; Mingyin Yao; Lin Huang (World Journal of Microbiology and Biotechnology, 2022)

Alternaria species causing leaf spot on hemp (Cannabis sativa) in Northern China - Hong Cheng; Lin Zhao; Xin Wei; Xi Liu; Guo-Yang Gao; Jian-Xin Deng; Mei-Jia Li (European Journal of Plant Pathology, 2022)

Extensive sequence divergence between the reference genomes of Taraxacum kok-saghyz and Taraxacum mongolicum - Tao Lin; Xia Xu; Huilong Du; Xiuli Fan; Qingwen Chen; Chunyan Hai; Zijian Zhou; Xiao Su; Liquan Kou; Qiang Gao; Lingwei Deng; Jinsheng Jiang; et al. (Science China Life Sciences, 2022)

Phylogeny and taxonomy of two new Alternaria (Ascomycota: Pleosporaceae) species in section Gypsophilae from China - Lin He; Hong Cheng; Aye Aye Htun; Hui Ge; Zhen Zhou Xia; Jian Wei Guo; Jian Xin Deng; Tao Du (Mycological Progress, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Simultaneously decreased temporal variability and enhanced variability-strength coupling of emotional network connectivities are related to positive symptoms in patients with schizophrenia - Yanjia Deng; Shuguang Han; Dongliang Cheng; Hui Li; Bin Zhang; Youyong Kong; Yong Lin; Yingjia Li; Ge Wen; Kai Liu (Brain Imaging and Behavior, 2021)

Transient Receptor Potential Ankyrin 1 Contributes to Lysophosphatidylcholine-Induced Intracellular Calcium Regulation and THP-1-Derived Macrophage Activation - Chao Tian; Rongqi Huang; Feng Tang; Zuoxian Lin; Na Cheng; Xiaobo Han; Shuai Li; Peng Zhou; Sihao Deng; Hualin Huang; Huifang Zhao; Junjie Xu; et al. (The Journal of Membrane Biology, 2020)

Atmospheric deposition and air–soil exchange of polybrominated diphenyl ethers (PBDEs) in a background site in Central China - Lingxi Zhan; Tian Lin; Hairong Cheng; Zuwu Wang; Zhineng Cheng; Deng Zhou; Zhengxin Qin; Gan Zhang (Environmental Science and Pollution Research, 2019)

Aflatoxin B1 enhances pyroptosis of hepatocytes and activation of Kupffer cells to promote liver inflammatory injury via dephosphorylation of cyclooxygenase-2: an in vitro, ex vivo and in vivo study - Li-Yin Zhang; Deng-Lin Zhan; Yuan-Yuan Chen; Wei-Hua Wang; Cheng-Yong He; Yi Lin; Yu-Chun Lin; Zhong-Ning Lin (Archives of Toxicology, 2019)

Occurrence of Bryde's whales, Balaenoptera edeni , in the northern Beibu Gulf, China - Mo Chen; Shiang‐Lin Huang; Haiping Wu; Zhigang Mei; Yiwen Chen; Jingsong Zheng; Wen Cheng; Keshun Deng; Chengteng Yang; Mao Chen; Chun‐Chieh Wang; Derun Lin; et al. (Marine Mammal Science, 2019)

Self-rooted grafting influences the growth and cadmium accumulation characteristics in the post generation of Cosmos sulphureus - Jin Wang; Yumei Tan; Ming’an Liao; Lijin Lin; Yi Tang; Huifen Zhang; Hui Xia; Dong Liang; Qunxian Deng; Xiulan Lv; Cheng Chen; Wei Ren (Environmental Science and Pollution Research, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Quantitative phosphoproteomic analyses provide evidence for extensive phosphorylation of regulatory proteins in the rhizobia–legume symbiosis - Zaibao Zhang; Danxia Ke; Menghui Hu; Chi Zhang; Lijun Deng; Yuting Li; Jiuli Li; Hai Zhao; Lin Cheng; Lei Wang; Hongyu Yuan (Plant Molecular Biology, 2019)

Cutting after grafting affects the growth and cadmium accumulation of Nasturtium officinale - Xingyu Zhang; Fenqin Zhang; Jin Wang; Lijin Lin; Ming’an Liao; Yi Tang; Guochao Sun; Xun Wang; Xiulan Lv; Qunxian Deng; Cheng Chen; Wei Ren (Environmental Science and Pollution Research, 2019)

Effects of Long-Term Application of Vinasse on Physicochemical Properties, Heavy Metals Content and Microbial Diversity in Sugarcane Field Soil - Juan Yin; Chao-Bing Deng; Xiao-Fei Wang; Gan-lin Chen; Viktor Gábor Mihucz; Gui-Ping Xu; Qu-Cheng Deng (Sugar Tech, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Effect of pad-fan cooling and dietary organic acid supplementation during late gestation and lactation on reproductive performance and antioxidant status of multiparous sows in hot weather - Jun Chen; Ji Guo; Wu-tai Guan; Jun-Jie Song; Zi-Xiao Deng; Lin Cheng; Yue-Lin Deng; Fang Chen; Shi-Hai Zhang; Yin-Zi Zhang; Fei Yang; Chun-Xiao Ren; et al. (Tropical Animal Health and Production, 2018)

Identifying potentially common genes between dyslipidemia and osteoporosis using novel analytical approaches - Xu Lin; Cheng Peng; Jonathan Greenbaum; Zhang-Fang Li; Ke-Hao Wu; Zeng-Xin Ao; Tong Zhang; Jie Shen; Hong-Wen Deng (Molecular Genetics and Genomics, 2018)

Effects of indole-3-butytric acid on lead and zinc accumulations in Pseudostellaria maximowicziana - Zhi Ran; Cheng Chen; Fabo Chen; Ming’an Liao; Lijin Lin; Xiulan Lv; Qunxian Deng; Xun Wang; Jin Wang; Yi Tang; Huaxiong Li (Environmental Monitoring and Assessment, 2018)

Development of a stable Japanese encephalitis virus replicon cell line for antiviral screening - Qiu-Yan Zhang; Xiao-Dan Li; Si-Qing Liu; Cheng-Lin Deng; Bo Zhang; Han-Qing Ye (Archives of Virology, 2017)

Morphology and controlling factors of the longitudinal profile of gullies in the Yuanmou dry-hot valley - Lin Ding; Fa-chao Qin; Hai-dong Fang; Hui Liu; Bin Zhang; Cheng-qiang Shu; Qing-chun Deng; Gang-cai Liu; Qian-qian Yang (Journal of Mountain Science, 2017)

Development of a fluorescence resonance energy transfer–based intracellular assay to identify novel enterovirus 71 antivirals - Wen-Wen Lu; Fang-Yen Kung; Po-An Deng; Yu-Chu Lin; Cheng-Wen Lin; Szu-Hao Kung (Archives of Virology, 2017)

Erratum to: Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Prolonged exposure to low-dose microcystin induces nonalcoholic steatohepatitis in mice: a systems toxicology study - Jun He; Guangyu Li; Jun Chen; Juan Lin; Cheng Zeng; Jing Chen; Junliang Deng; Ping Xie (Archives of Toxicology, 2017)

Imperatorin inhibits the expression of alpha-hemolysin in Staphylococcus aureus strain BAA-1717 (USA300) - Ping Ouyang; Junjie Chen; Mao Sun; Zhongqiong Yin; Juchun Lin; Hualin Fu; Gang Shu; Changliang He; Cheng Lv; Xuming Deng; Kaiyu Wang; Yi Geng; et al. (Antonie van Leeuwenhoek, 2016)

A retrospective study of the occurrence of ischemic-type biliary lesions post liver transplantation - Rui Shi; Ya-Min Zhang; Yong-Lin Deng; Hong Zheng; Cheng Pan; Zhong-Yang Shen (Science China Life Sciences, 2016)

The Longmala and Mengya’a skarn Pb–Zn deposits, Gangdese region, Tibet: evidence from U–Pb and Re–Os geochronology for formation during early India–Asia collision - Liqiang Wang; Juxing Tang; Jun Deng; Haoran Kang; Xin Lin; Wenbin Cheng; Zhuang Li; Zhi Zhang (International Geology Review, 2015)

Conjugated linoleic acid alters growth performance, tissue lipid deposition, and fatty acid composition of darkbarbel catfish (Pelteobagrus vachelli) - Gui-Fang Dong; Wen-Zuo Liu; Lin-Zhou Wu; Deng-hang Yu; Feng Huang; Peng-Cheng Li; Yan-ou Yang (Fish Physiology and Biochemistry, 2015)

Seasonal characteristics and tetrodotoxin-producing ability of bacteria in gastropod Oliva hirasei - Chun-Lan Lin; Ya-Jung Wu; Wen-Feng Lin; Cheng-Hong Hsieh; You-Liang Hsieh; Deng-Fwu Hwang (Hydrobiologia, 2014)

Hesperetin protects against cardiac remodelling induced by pressure overload in mice - Wei Deng; Duan Jiang; Yi Fang; Heng Zhou; Zhihong Cheng; Yafen Lin; Rui Zhang; Jieyu Zhang; Peng Pu; Yuan Liu; Zhouyan Bian; Qizhu Tang (Journal of Molecular Histology, 2013)

Comparative study on debris flow initiation in limestone and sandstone spoil - Ning-sheng Chen; Yang Lu; Ming-feng Deng; Da-wei Han; Hai-bo Zhou; Cheng-lin Yang (Journal of Mountain Science, 2013)

A single amino acid substitution in PthA of Xanthomonas axonopodis pv. citri altering canker formation on grapefruit leaves - Hsin-Cheng Lin; Mu-Kuei Chu; Yuang-Chuen Lin; Wen-Ling Deng; Hsiang Chang; Shih-Tien Hsu; Kuo-Ching Tzeng (European Journal of Plant Pathology, 2011)

High prevalence of a novel porcine bocavirus in weanling piglets with respiratory tract symptoms in China - Shaolun Zhai; Cheng Yue; Zuzhang Wei; Jinxue Long; Duoliang Ran; Tao Lin; Yu Deng; Lv Huang; Lichang Sun; Haihong Zheng; Fei Gao; Hao Zheng; et al. (Archives of Virology, 2010)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Complete sequence of a subgroup 3.4 strain of classical swine fever virus from Taiwan - Yu-Ju Lin; Maw-Sheng Chien; Ming-Chung Deng; Chin-Cheng Huang (Virus Genes, 2007)

An efficient protocol for genomic DNA extraction fromCitrus species - Yun-Jiang Cheng; Wen-Wu Guo; Hua-Lin Yi; Xiao-Min Pang; Xiuxin Deng (Plant Molecular Biology Reporter, 2003)